THE CONSTITUTION OF THE FEDERAL REPUBLIC OF NIGERIA, 1999: ANALYZING THE QUEST FOR AN AUTOCHTHONOUS CONSTITUTION - E. Odike, Adakole; Philip Faga, Hemen; Ogwuche, Enenche Matthew (Gapenas Publisher, 2024)
Nigeria is a multi-cultural, multi-ethnic and multi-religious country pieced together by the British colonial administration. Although, the country has remained one indivisible and indissoluble entity, the different regions maintain their distinct identities, and work towards varied aspirations. However, the current 1999 constitution of Nigeria, which is a product of the military administration that ruled Nigeria from 1983 to 1999, seems to create a federal system that disregard the diversities of the country and concentrate power in the center (federal government); yet, it purports in its preamble to be a constitution given by the people of Nigeria. Using the doctrinal approach, this paper appraised the claim of the 1999 constitution as a people-driven document against the backdrop of an autochthonous constitution. It found that the 1999 Nigerian constitution (as amended) lacks legitimacy as an autochthonous constitution because of the absence of participation of the people in the constitution-making process, and the fact that it was midwife by an illegal and unconstitutional military government. The paper also identified the features of the constitution that expose the arbitrariness of the military in foisting a constitution on the people of Nigeria without consensus, such as the over-concentration of revenue generating powers and revenue sharing in the center, and neglect of the federating states. The paper concluded that the Nigerian National Assembly should commence the process of making a new autochthonous constitution for the country to overturn the current 1999 constitution. It recommended that the new constitution should decentralize power to the federating states of Nigeria to meet the yearnings of the different regions of Nigeria.